2001
DOI: 10.1063/1.1344888
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum–ultraviolet absorption and fluorescence spectroscopy of CF2H2, CF2Cl2, and CF2Br2 in the range 8–22 eV

Abstract: The vacuum-UV absorption and fluorescence spectroscopy of CF 2 X 2 (X=H,Cl,Br) in the range nm is reported. Tunable vacuum-UV radiation in the range 8-22 eV from synchrotron sources at either Daresbury, UK or BESSY1, Germany is used to excite the titled molecules. Fluorescence excitation spectra, with undispersed detection of the fluorescence, were recorded at Daresbury with a resolution of 0.1 nm. VUV absorption spectra at a resolution of 0.08 nm, and dispersed emission spectra with an optical resolution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
12
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 62 publications
7
12
1
Order By: Relevance
“…The assignments of the principal features have been taken from [37] and are included in figure 5. In some cases, these assignments do not match those proposed by Seccombe et al [38] but the differences are not relevant to the present work.…”
Section: Dichlorodifluoromethanecontrasting
confidence: 85%
“…The assignments of the principal features have been taken from [37] and are included in figure 5. In some cases, these assignments do not match those proposed by Seccombe et al [38] but the differences are not relevant to the present work.…”
Section: Dichlorodifluoromethanecontrasting
confidence: 85%
“…The calculated VUV spectrum using EOMCCSD/aug-cc-pVTZ + 4s + 4p in the energy range of 8-13 eV is shown in Fig. 16, compared with the observed VUV spectrum by Seccombe et al 40) The peak maximum (9.6 eV) of the calculated first band is slightly higher than the observed one (9.2 eV). This may be due to the excited-state potential curves.…”
mentioning
confidence: 71%
“…[31][32][33] However, the hydrofluorocarbon gas chemistries, as exemplified by CH 2 F 2 , are representative of fragments such as CHF, CH 2 F, and CHF 2 , leading to differences in etching performance for SiN. [34][35][36][37][38] VUV absorption spectroscopy of CH 2 F 2 in the range of 60-145 nm was reported by Sauvageau et al 39) and absorption and fluorescence spectroscopy of CF 2 F 2 in the range of 190-690 nm was reported by Seccombe et al 40) They reported the first band (peak value of 9.28 eV) and fourth band (peak value of 12.38 eV) are structureless. In the latter report, excited to the first band with a peak value of 9.28 eV, emission due to the CF 2 1 B 1 -1 A 1 transition was observed.…”
Section: Electronic Properties Of Ch 2 Fmentioning
confidence: 99%
“…Our ionization energy (IE) range is 12-20 eV. A variety of fragmentation processes [4][5][6][7][8][9][10] compete with direct ionization within that range although these degradations are not expected to be visible in conventional photoelectron spectra. These processes have been summarised in threshold photoelectronphotoion coincidence (TPEPICO) studies 6 on the dissociation of CH 2 F 2 + .…”
Section: Introductionmentioning
confidence: 99%